2011
DOI: 10.1186/2042-6410-2-2
|View full text |Cite
|
Sign up to set email alerts
|

The innate immune response to coxsackievirus B3 predicts progression to cardiovascular disease and heart failure in male mice

Abstract: BackgroundMen are at an increased risk of dying from heart failure caused by inflammatory heart diseases such as atherosclerosis, myocarditis and dilated cardiomyopathy (DCM). We previously showed that macrophages in the spleen are phenotypically distinct in male compared to female mice at 12 h after infection. This innate immune profile mirrors and predicts the cardiac immune response during acute myocarditis.MethodsIn order to study sex differences in the innate immune response, five male and female BALB/c m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 43 publications
4
59
0
Order By: Relevance
“…The importance of TLR4 signaling in a strictly autoimmune model of myocarditis was demonstrated by Nishikubo et al where TLR4 signaling was found to be necessary to mount a Th1-type immune response (Nishikubo et al, 2007). We have shown that TLR4 is upregulated on macrophages and mast cells during the innate immune response to CVB3 and during acute CVB3 myocarditis and this response results in increased inflammation and progression to DCM and HF in males compared to females (Frisancho-Kiss et al, 2007;Onyimba et al, 2011). A Th1 response in male mice was found to be due to TLR4-derived IL-18, which was originally named IFN--inducing factor, rather than to a classical IL-12/STAT4-induced Th1 response .…”
Section: Cytokines: Tnf Il-1 and Il-18supporting
confidence: 52%
“…The importance of TLR4 signaling in a strictly autoimmune model of myocarditis was demonstrated by Nishikubo et al where TLR4 signaling was found to be necessary to mount a Th1-type immune response (Nishikubo et al, 2007). We have shown that TLR4 is upregulated on macrophages and mast cells during the innate immune response to CVB3 and during acute CVB3 myocarditis and this response results in increased inflammation and progression to DCM and HF in males compared to females (Frisancho-Kiss et al, 2007;Onyimba et al, 2011). A Th1 response in male mice was found to be due to TLR4-derived IL-18, which was originally named IFN--inducing factor, rather than to a classical IL-12/STAT4-induced Th1 response .…”
Section: Cytokines: Tnf Il-1 and Il-18supporting
confidence: 52%
“…Sections (5 m thick) were stained with hematoxylin and eosin or with Masson's trichrome to detect inflammation or fibrosis, respectively. Myocarditis and fibrosis were assessed as the percentage of the heart section with inflammation or fibrosis compared with the overall size of the heart section using an eyepiece grid at low power (ϫ25), as previously described (9,15,16,19,37). Collagen deposition using Masson's trichrome stains an intensely "baby blue" color compared with inflammation, which appears as dark blue.…”
Section: Methodsmentioning
confidence: 99%
“…Cardiac function and ventricular dilation were assessed by transthoracic echocardiography (Acuson Sequoia C256, 15-MHz linear transducer, Siemens, Malvern, PA) in conscious mice, as previously described (9,37). The M-mode LV end-systolic crosssectional diameter was determined from an average of three to five cardiac cycles.…”
Section: Methodsmentioning
confidence: 99%
“…According to these models, the inner surface of the channel formed by the TSPO molecule would present a hydrophilic but uncharged pathway, allowing amphiphilic cholesterol molecules to cross the outer mitochondrial membrane (Papadopoulos et al, 1997(Papadopoulos et al, , 2006Veenman et al, 2007). At cellular levels TSPO is present in virtually all of the cells of the cardiovascular system, where they appear to take part in the responses to various challenges that an organism and its cardiovascular system face (Veenman & Gavish, 2006), including atherosclerosis and accompanying symptoms (Onyimba et al, 2011;Bird et al, 2010;Dimitrova-Shumkovska et al, 2010a,b,c, 2012.…”
Section: The 18kda Translocator Protein (Tspo) and Apolipoprotein Ementioning
confidence: 99%